22nd Symposium on Composites : selected, peer reviewed papers from the "22nd Symposium on Composites," June 26-28, 2019, Kaiserslautern, Germany - Hausmann, Joachim M. (Trans Tech Publications, 2019)
The "22nd Symposium on Composites", held in the science city of Kaiserslautern, Germany, from June 26-28, 2019, covered a wide range of composite-related topics including polymer, metal and ceramic matrix composites, hybrid structures and materials, coatings, manufacturing technologies, testing and simulation, smart materials, biocomposites and recycling. This conference was organized by the "Gemeinschaftsausschuss Verbundwerkstoffe (GAV)" within the "Deutsche Gesellschaft für Materialkunde e.V. (DGM)" in cooperation with the "Institut für Verbundwerkstoffe GmbH (IVW)" and the University of Kaiserslautern. Researchers from different scientific institutions and technology companies presented and discussed the latest developments and trends in all kinds of composites. Bio Composites, Coatings, Hybrid Structures and Materials, Manufacturing Technologies, Metal and Ceramic Matrix Composites, Polymer, Recycling, Smart Materials, Testing and Simulation Materials Science, Building Materials, Mechanical Engineering.
Keywords: Composite materials -- Congresses.; Composite materials -- Analysis -- Congresses.; elektronické knihy; electronic books